Interview with Consuelo Guerri (Journal of Parents and Teachers, 2014)
The beginning of alcohol consumption among teenagers is between 13 and 14. Some of these don’t know how to control themselves and don’t know that drinking because of drinking slows down their cerebral development. In addition the sooner they start drinking alcohol without control means more risk to future addictions. Therefore they must know that if there is no control they will have difficulties in their neuronal maturing.
Keywords: interview; alcoholism and adolescence; dependency; development problems.